Complex Therapy for Intraoperative Blood Loss during Pelvic Bone Repair - Z. G. Marutyan; Yu. V Nikiforov; A. B. Kazantsev; A. A. Ter-Grigoryan (Общая реаниматология)
Objective: to introduce blood saving technologies and to develop algorithms for management of patients with pelvic fractures. Subjects and methods. Sixty patients aged 40.6±2.3 years with pelvic fractures were examined. The banking of packed autoerythrocytes and auto freshly frozen plasma (AutoFFP), intraoperative acute hypervolemic hemodilution (AHH), and instrumental reinfusion of washed autoerythrocytes were made in all the patients. Blood loss volume averaged 32.1±1.7 ml/kg. The parameters of central hemodynamics (CH), blood oxygen-transport function, the blood system (red blood cells, hemoglobin, packed cell volume, and platelets) were studied. AutoFFP was transfused in the most traumatic period of surgery, autoblood was on completion of surgical hemostasis, and washed autoerythrocytes were within 3—4 hours after surgery. Postoperative reductions in hemoglobin to below 80 g/l and packed cell volume below 25% are indications for packed autoerythrocyte transfusion. Results. During preoperative autoblood banking, the parameters of CH and the blood system underwent no changes, all variations in the parameters were within the normal range and compensatory. When AHH and instrumental washed erythrocyte reinfusion were conducted, there was a significant increase in cardiac index (CI), stroke index by 37 and 30%, respectively; reductions in total peripheral vascular resistance index by 38%, mean blood pressure by 18%, moderate hypercoagulation, and significant decreases in hemoglobin, packed cell volume, red blood cells by 17, 15, and 18%, respectively. The values of acid-base condition and homeostasis underwent no considerable changes. Arterial blood O2 content was significantly lowered by 16%; however, global O2 uptake remained unchanged at the baseline levels due to the increase of CI by 30% of the baseline level. Conclusion. The application of blood saving technologies, preoperative autoblood banking in particular, AHH, and instrumental washed autoerythrocyte reinfusion allowed a refusal to use allo-geneic blood components during pelvic repair, by preventing the development of hemotransfusion complications. Key words: blood loss, blood saving, packed autoerythrocytes, auto freshly frozen plasma, acute hypervolemic  hemodilution, autohemotransfusion, instrumental washed autoerythrocyte reinfusion, spinal epidural anesthesia.